ANALYSIS OF THE EFFECT OF MARKETING MIX ON CONSUMER TRUST AND SATISFACTION ON ONLINE PURCHASING OF ORGANIC FOOD DURING THE OUTBREAK OF THE COVID-19 - Maulana, Syahrizal; Najib, Mukhamad; Sarma, Ma’mun (Universitas Brawijaya, Indonesia, 2021)
The internet changes people's consumption patterns and shopping behavior. Online shopping activities can be done without leaving the house and can be done at any time. Online purchases are increasing during the pandemic due to Covid-19. Organic food business players can use internet marketing activities to attract more consumers, and one way that can be used is a marketing mix. This study analyzes the effect of the marketing mix on consumer trust and satisfaction in purchasing organic food online to increase repurchase intention. The population in this research is organic food consumers. The sample was taken using a purposive sampling method that targets consumers who live in the Jabodetabek area through an online questionnaire survey. Respondents who meet the criteria are 200 consumers. Structural Equation Modeling (SEM) was used in data processing and analysis. The results showed that the product and place had a significant effect on consumer satisfaction. Trust has a significant impact on satisfaction but had no significant effect on repurchase intention. Satisfaction had a significant effect on the repurchase intention of organic food. The suggestion for further research needs to analyze the types of organic rice, vegetables, and fruits purchased by consumers in more detail.